Arthroscopic partial repair versus debridement combined with acromioplasty alone for irreparable rotator cuff tears in the elderly - Li, Ning; Sun, Lu; Zhang, Zhongyuan; Kang, Hanwei; Jiang, Hongjiang; Qin, Liwu (Frontiers in Surgery, 2025)
ObjectiveTo compare postoperative outcomes of arthroscopic partial repair vs. debridement combined with acromioplasty in elderly patients with irreparable rotator cuff tears, focusing on pain relief, functional improvement, and quality-of-life enhancement.MethodsBetween January 2019 and March 2022, 41 patients (partial repair group, n = 21; debridement group, n = 20) with irreparable rotator cuff tears were prospectively enrolled. Functional outcomes [Constant-Murley Score [CMS], University of California Los Angeles Score [UCLA]) were assessed preoperatively and 12 months postoperatively. Visual Analog Scale (VAS) scores were recorded at 2 and 6 weeks. Magnetic resonance imaging (MRI) and anteroposterior x-rays were used to measure global fatty degeneration index (GFDI) and acromiohumeral distance (AHD). Tendon healing was evaluated using the Sugaya classification system.ResultsAll surgeries were completed without complications. Follow-up averaged 14.1 months (range, 12–18 months). Postoperative CMS (partial repair: 43.57–70.86 vs. debridement: 42.55–58.95) and UCLA scores (partial repair: 8.67–21.43 vs. debridement: 8.30–18.40) improved significantly in both groups (P < 0.05), with greater enhancements in muscle strength and range of motion favoring partial repair. VAS scores were higher in the partial repair group at 2 weeks (3.1 ± 0.8 vs. 2.1 ± 0.7, P < 0.05) but equivalent at 6 weeks (P > 0.05). Postoperative GFDI increased in both groups (P < 0.05) without intergroup differences. AHD remained stable in the partial repair group (P > 0.05) but decreased in the debridement group (P < 0.05), with higher AHD persisting in the partial repair subgroup (P < 0.05). Subgroup analysis revealed no differences in outcomes between re-tear and non-re-tear patients. Preoperative AHD correlated positively with postoperative CMS and UCLA scores (P < 0.05), while Sugaya classification and preoperative GFDI showed no association with functional outcomes.ConclusionArthroscopic partial repair yielded superior functional outcomes compared to debridement combined with acromioplasty in elderly patients with irreparable rotator cuff tears, particularly enhancing shoulder strength and range of motion while preserving AHD. Early postoperative pain should be anticipated. Preoperative AHD emerged as a predictor of functional recovery.